Outcome trajectories in a county mental health clinic before and after telemental health: a retrospective COVID-19 cohort study - Harris, Bethany A.; Aajmain, Syed; Scharff, Adela; Boswell, James F. (Frontiers in Psychology, 2023)
Background/Objectives: Telemental health (TMH) care has received increased attention, most recently due to the COVID-19 pandemic. Many treatment settings and clinicians were forced to rapidly shift to TMH modalities, including clinicians with limited exposure to and possibly negative attitudes toward alternative treatment delivery formats. With the shift to new modalities, effectiveness research is necessary to understand if patients are receiving the same quality of care as before the pandemic and their receipt of mostly in person services. This study compared the naturalistic treatment outcome trajectories for a cohort of patients who received in-person services prior to the pandemic and a distinct cohort of patients who received TMH services after the onset of the pandemic, in a community mental health setting with limited exposure to TMH prior to the COVID-19 pandemic. Materials and methods: We adopted a retrospective cohort design to examine treatment modality as a between-group moderator of symptom change trajectory on the self-report Patient Health Questionnaire (PHQ-9) in a sample of N = 958 patients in the Northeast United States. Treatment durations differed in the naturalistic treatment setting and we examined patient-reported outcomes up to a maximum of one year. Results: Statistically significant average decreases in symptom severity were found over the course of up to one year of treatment, yet the average outcome trajectory was not significantly different between two modality cohorts (in person delivery before the pandemic versus TMH delivery after pandemic onset). Conclusion: These findings suggest that even in a setting with limited exposure to or training in TMH, the average outcome trajectory for patients who received TMH was statistically similar to the outcome trajectory for patients in an earlier cohort who received in-person services prior to the pandemic onset. Overall, the results appear to support continued use of TMH services in community treatment settings.